Indicator Carbon-Paste Electrode for Voltammetric Analysis - Dmitry Aronbaev; Sergey Aronbaev; Dilnoza Isakova (Engineering Proceedings, 2023)
The design of an indicator electrode made of carbon paste of ergonomic design for the voltammetric determination of a number of substances of inorganic and organic origin is described. The electrode is made of a graphite rod with a diameter of 6 mm and a length of 70 mm, covered with insulation, and having a cavity filled with an electroactive carbon-containing material at the end of the rod. The characteristic features of the proposed electrode—the insulating shell of the housing made of shrink tubing and the electrolytic coating of the cavity surface with a conductive metal film—make it possible to simplify the design of the electrode and increase mechanical strength, extend the service life of the electrode, and also provide the possibility of volumetric and surface modifications with an economical consumption of modifying reagents. Examples of the use of an indicator electrode modified with mercury and bismuth films and volumetrically modified with manganese dioxide nanoparticles in the analysis of food, beverages, natural objects for the content of heavy metal ions, pharmaceuticals for the content of hydrogen peroxide, and vitamins of groups B and C are given. The simplicity of making the developed indicator electrode from carbon paste and its mechanical strength and cost-effectiveness when using expensive and scarce modifiers allow us to recommend it for use in voltammetric analysis and the creation of various biosensor systems.